A relação entre a prosa e a poesia no Livro do Desassossego - Silva, Sâmila Maria Oliveira da (2021)
The present work seeks to show how poetry appears in the prose of the Livro do Desassossego, by Fernando Pessoa, making it characterized as a poetic prose. The work corresponds to a set of fragments written by Pessoa and collected by scholars from the author's unpublished collection, which began to publish them in book format from 1982. In these fragments, Pessoa builds a prose based on poetic images, figures of rhetoric and rhythm. Thus, treating a narrowing between the poetry and prose of the book and evokes analogies that bring the reader closer to the sensations experienced by the semi-heteronym Bernardo Soares, fictional author of the book. These sensations are mainly related to issues of conscience, boredom and the subject who finds himself torn and stagnant in the face of the modern world. And they arise due to the reflexive game that the author negotiates between the thinking subject (I) and the thought object (not me), so dear to Portuguese Modernism. Therefore, the research proposes an analysis of poetic images, rhetorical figures and rhythm that emerge along the fragments. Therefore, it is based especially on the theoretical assumptions of Massaud Moisés in the books A Criação Literária: Poesia (1998) and A Criação Literária: Prosa II (1998), Octavio Paz in the books O Arco e a lira (1982) and Signos em rotação (2009), José Luiz Fiorin in the book Figuras de retórica (2014) and Gaston Bachelard, in A Poética do Devaneio (2006) and A poética do espaço (1993).